Design and implementation of 100 news of the hour - Chua, Willy Wee Siong. (2010)
Really Simple Syndication (RSS) and Atom consists of web feed formats that are used to publish frequently updated works such as blog entries, news headlines, audio, and video in a standardised format. It has enabled publishers to syndicate their content automatically with the latest information in a summarise form. Users who are interested in certain content are required to subscribe to a publisher feed to get the latest information.